(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2020)
Underscrutinized psalms of 93, 100, 121, 126 and 128 are underlaying and performing the very essence of the God of Israel as the merciful, loving and liberating God. Nothing is to lose with the God of Israel. The essence of the God of Israel as the eternal King (Ps.93), the faithful Keepguarder (Ps. 121) and the Hope of Israel (126) provokes and invites the people of Israel to hail and to adore Him in His Holy Place (Ps. 100) in order to get and to inherit His plentiful Blessings (Ps. 128). In other words, those who have the holy fear to God and faithfully obeying His commandments deserve God’s blessings. On these theological perspectives we have investigated the Catholic parishioners and its leaders of St. Peter and Paul’s half Parish - Oesapa, to find out howfar they have performed and embodied the mercy of God and obeying His commandments. And they are making effort and advancing in serving the Church and obeying the God’s commandments.